2001
DOI: 10.1002/1521-3951(200111)228:2<457::aid-pssb457>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Optical Properties of AlN, GaN, and InN Compounds under Hydrostatic Pressure

Abstract: We present first-principles full-potential linearized augmented plane wave calculations of the effect of hydrostatic pressure on the optical properties of wurtzite GaN, InN and AlN compounds. The refractive index and its variation with hydrostatic pressure are well described. The accurate calculation of linear optical function (refraction index and its pressure derivative, and both imaginary and real parts of dielectric function) is performed in the photon energy range up to 30 eV. The predicted optical consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…4, we obtain relative pressure coefficients ð1=e 1 Þde 1 =dP of À8.8 Â 10 À3 GPa À1 and À14.8 Â 10 À3 GPa À1 for w-InN and rs-InN, respectively. These values, together with theoretical results from different works, 1,2,4,5 are displayed in Table I. As can be seen in the table, for w-InN, our experimental (1/e 1 )de 1 /dP values agree well with the lowest range of reported theoretical values (Ref.…”
supporting
confidence: 84%
“…4, we obtain relative pressure coefficients ð1=e 1 Þde 1 =dP of À8.8 Â 10 À3 GPa À1 and À14.8 Â 10 À3 GPa À1 for w-InN and rs-InN, respectively. These values, together with theoretical results from different works, 1,2,4,5 are displayed in Table I. As can be seen in the table, for w-InN, our experimental (1/e 1 )de 1 /dP values agree well with the lowest range of reported theoretical values (Ref.…”
supporting
confidence: 84%
“…These are the most common wurtzite, rock-salt or cubic structures [29]. Of these structural forms, several fundamental calculations [30][31][32] have indicated that the lowest energy phase is the wurtzite structure with the zinc-blende phase only marginally higher in energy.…”
Section: Computationalmentioning
confidence: 93%
“…These devices have wide applications in rapidly growing semiconductor technology such as optical-fiber communication networks, compact disk opticalstorage technology, laser printers as well as in automobile industry. Each of the nitride materials has high ionicity, high bond strength and good thermal conductivity [2] and are candidates for high power and high temperature device applications. Wurtzite materials have direct energy gap ranging from 6.1 eV [3] for A1N, 3.5 eV [3] for GaN, and 0.8 eV [4] for InN.…”
Section: Introductionmentioning
confidence: 99%